PENGARUH MODEL PEMBELAJARAN INKUIRI BERBANTUAN MEDIA KAPINDO (KANTONG PINTAR DORAEMON) TERHADAP HASIL BELAJAR MATEMATIKA - Meida Maghfiroh; Khamdun; Nur Fajrie (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose in this study is to know the average difference in students' mathematics learning outcomes after applying the inquiry learning model with KAPINDO media. This type of research is a pre-experimental design with a one-group pretest-posttest design. This research was conducted in class V SD 6 Klumpit. The sample in this study were 24 students. There are two variables, the independent variable, namely the inquiry learning model with KAPINDO media, and the dependent variable used, namely student learning outcomes. This type of research is quantitative research. The data analysis technique used was the paired sample t-test on the pretest and posttest results with a significance value (2-tailed) of 0.000 <0.05. The results showed that the application of the inquiry learning model with KAPINDO media had an influence on students' mathematics learning outcomes, with an average student mathematics learning result before being given treatment of 58.58 and after using the inquiry learning model with KAPINDO media of 82.42. The difference in the average results has a difference of 23.84 which shows a significant effect on students' mathematics learning outcomes.